Macronutrient and Sensory Analysis of Block, Crystal, and Liquid Coconut Sugar - Cassandra Permata Nusa; Rimbawan Rimbawan (Universitas Negeri Malang, 2022)
This study aimed to determine the nutritional content of the block, crystal, and liquid coconut sugar, along with the preferred coconut sugar type, through sensory analysis. The design of this research was descriptive analysis. The nutrient content analysis method was carried out proximately, while sensory analysis used a hedonic test and a hedonic quality test. The results showed that crystal coconut sugar had the highest energy, fat, protein, and carbohydrate content of 377 kcal/100g, 0.56 percent, 1.29 percent, and 91.7 percent, respectively. Block coconut sugar presented energy of 363.14 kcal/100g, 0.46 percent fat, 1.2 percent protein, and 88.55 percent carbohydrates. Meanwhile, liquid coconut sugar showed 293.7 kcal/100g of energy, 0.22 percent fat, 1.24 percent protein, and 71.69 percent carbohydrates. The results of the sensory analysis showed no significant differences between each form of coconut sugar in aroma (p=0.66) and texture (p=0.08) elements from the hedonic test. Additionally, there were significant differences in the color and taste attributes (p=0.00). Contrastingly, the hedonic quality test showed significant differences in all attributes of all forms of coconut sugar. Besides, crystal coconut sugar was preferred over the block and liquid coconut sugar. It has a slightly typical brown sugar aroma, insignificant fine to fine texture, dark brown to light brown color, and slightly sweet to sweet taste. Therefore, crystal coconut sugar is the most preferred form with the highest nutritional content.